PENGARUH EFISIENSI OPERASIONAL DAN KREDIT BERMASALAH TERHADAP KINERJA KEUANGAN: BUKTI EMPIRIS DARI INDUSTRI PERBANKAN - Enang Suherman; Ida Jalilah Fitria (Yayasan Insani Mandiri Santani, 2026)
This study aims to examine and analyze the effect of operational efficiency, proxied by the Operating Expenses to Operating Income ratio (BOPO), and credit risk, proxied by the Non-Performing Loan (NPL) ratio, on banking financial performance measured by Return on Assets (ROA). The population in this study covers all conventional banking institutions listed on the Indonesia Stock Exchange (IDX). Using a purposive sampling method, samples were selected based on consistent financial reporting and consecutive publications during the observation period. The data analysis method employed is multiple linear regression analysis to test the variables both partially and simultaneously. The theoretical framework of this research is rooted in Stewardship Theory to explain the BOPO efficiency ratio, as well as Information Asymmetry Theory and Risk-Return Trade-Off Theory to explain the NPL credit risk variable. The partial results indicate that BOPO has a negative and significant effect on ROA, suggesting that high operational inefficiency decreases bank profitability. Similarly, NPL exhibits a negative and significant effect on ROA, signifying that an accumulation of non-performing loans forces banks to increase provision costs, which erodes net profit. Simultaneously, BOPO and NPL exert a significant effect on banking financial performance. These findings provide practical contributions for bank management in formulating integrated risk mitigation strategies in the era of financial digitalization to maintain profitability stability. Keywords: BOPO, Financial Performance, Non-Performing Loan (NPL), Return on Assets (ROA), Banking.